Essentials of Marketing Research - Hawkins Del I; Tull Donald S; Macmillan Company (1994)
The Nature of Marketing Research, The Sources of Research Data, Measurement Techniques in Marketing Research, Sampling and Data Analysis, Marketing Research Reports and Ethical Issues, Indexes.
The Nature of Marketing Research, The Sources of Research Data, Measurement Techniques in Marketing Research, Sampling and Data Analysis, Marketing Research Reports and Ethical Issues, Indexes.